Pangola (Digitaria eriantha) Hay as a Roughage Source in Total Mixed Ration (TMR) on Growth Performance and Meat Quality of Thai Native Male Goats in a Tropical Area - Wiyabot, T. , (International Journal of Agricultural Technology, 2018)
The productivity and chemical composition of Pangola grass during rainy and dry seasons. Results revealed to be used Pangola grass as a roughage source in the total mixed ration (TMR) for growth performance and meat quality of Thai native male goats in the tropics. Temperature was recorded as well as maximum and minimum relative humidity. The first experiment included recording the productivity and analysing the chemical composition of DM, CP, Ash, EE, CF and NFE of Pangola grass during the rainy and dry seasons of 2013-2015. The second experiment that involved classifying fertilized male goats weighing 15 ± 2 kg. into 3 groups. Each group contained 5 goats, and the classification was repeated 3 times for 45 goats in total. Group 1 had straw as a roughage source in the total mixed ration (TMR1). Group 2 used bean hulls as a roughage source in the total mixed ration (TMR2), and Group 3 used Pangola grass hay as a roughage source in the total mixed ration (TMR3). The ratio between roughage and concentrated feed was 15:85 with an average protein content of 14% CP to record the production efficiency and meat quality. The results showed that in the first experiment, the total dry matter yield of Pangola and chemical composition in winter were higher compared to summer due to the propensity of declining yield as the plants aged. For the second experiment, the ADG and CPI of Pangola grass hay (TMR3) were significantly higher than the values for straw (TMR1) and bean hulls (TMR2) (P<0.05), whereas for total gain, TDMI, feed conversion ratio, blood urea nitrogen, feed cost, carcass traits, qualities and consumer preference, tests of the goat meat did not show any significant differences (P>0.05)